2016
DOI: 10.1002/anie.201605999
|View full text |Cite
|
Sign up to set email alerts
|

Efficient O‐Functionalization of Carbohydrates with Electrophilic Reagents

Abstract: Novel methodology for O‐functionalization of carbohydrate derivatives has been established using bench‐stable and easily prepared iodonium(III) reagents. Both electron‐withdrawing and electron‐donating aryl groups were introduced under ambient conditions and without precautions to exclude air or moisture. Furthermore, the approach was extended both to full arylation of cyclodextrin, and to trifluoroethylation of carbohydrate derivatives. This is the first general approach to introduce traditionally non‐electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 76 publications
0
34
0
Order By: Relevance
“…[7] Our research group has gained considerable experience in metal-free arylations with these reagents using O-, N-and Ccentered nucleophiles. [8] While most of these have been efficiently arylatedb yt he ligand couplingp athway,s everal intriguing indications on alternative reactionp athways have been observed, for example, by formation of regioisomeric products and oxidized byproducts. Mechanistic insights to these fascinating observations would aid further developments with diaryliodonium salts and other iodine(III) reagents, and we thus initiated an investigation on competing pathways in O-arylations using both experimental techniques and DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Our research group has gained considerable experience in metal-free arylations with these reagents using O-, N-and Ccentered nucleophiles. [8] While most of these have been efficiently arylatedb yt he ligand couplingp athway,s everal intriguing indications on alternative reactionp athways have been observed, for example, by formation of regioisomeric products and oxidized byproducts. Mechanistic insights to these fascinating observations would aid further developments with diaryliodonium salts and other iodine(III) reagents, and we thus initiated an investigation on competing pathways in O-arylations using both experimental techniques and DFT calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,b reakthroughs in the direct O-arylation of free hydroxy groups in carbohydrates by the use of electrophilic arylating agents have been reported. [11] In these reactions, however, strong bases are used, and extensive protection of all other hydroxy groups seems to be necessary to avoid overarylation.…”
mentioning
confidence: 99%
“…After initial optimization (see Table S1), it was found that the target di‐ p ‐tolyliodonium triflate ( 4 a ) could be obtained, after only a two‐seconds residence time, in excellent yield (89 %) after crystallization (Table ). Notably, our flow protocol was highly reproducible and the yields were typically higher than those obtained with conventional batch labware (52–67 %) . The procedure can be readily scaled and, as an example, we obtained 2.04 grams of 4 a (5 mmol scale, 89 %).…”
Section: Methodsmentioning
confidence: 82%